Sistema Impro com crianças: experiência de ensino-aprendizagem do teatro na educação fundamental - Hortencia Campos Maia (2015)
This paper presents a teaching experience report of the practice of the Impro System in a Drama as school subject. Students were on 4th and 5th grade of the Brazilian Elementary School (ages 9-10) in a school in the city of Belo Horizonte. The report consists of ethnography of experience of the researcher and children, through observation, narrative and analysis of the practice. Impro System is a teaching-learning improvisation system, created by Keith Johnstone and developed from the 1950s until today. His idea is premised on the release of imagination and creativity to do spontaneous theater and has been gradually used and discussed by artists-researchers-teachers in Brazil. However, in the context of Drama learning in Basic Education, a gap is noticed regarding this practice and academic discussions to set it a possible methodology for teaching Theater at school. Thus, this experience may contribute to the broadening of knowledge about Impro System not only to its practitioners and Drama teachers, but also to theater learning in Elementary School, from the childrens point of view.